2011
DOI: 10.1007/s11695-011-0454-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy in Patients over 59 Years: Early Recovery and 12-Month Follow-Up

Abstract: Background Bariatric surgery has shown to be safe for patients over 60 years with good results especially considering resolving of comorbidities. Sleeve gastrectomy is considered to be safer than gastric bypass (GBP) and more effective than gastric banding with less adverse symptoms. Weight loss may be more modest than after GBP, but the effect on vitamins may also be milder. Methods Since 2007, we collected prospectively 12-month follow-up data from 55 sleeve gastrectomy patients of whom 12 were over 59 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
2
36
1
1
Order By: Relevance
“…11,17,18 However, recent studies have shown that bariatric surgery in older patients is as safe and effective for weight loss as for younger patients. [12][13][14][15]19 The present study showed no significant differences in %EWL in patients across age groups.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…11,17,18 However, recent studies have shown that bariatric surgery in older patients is as safe and effective for weight loss as for younger patients. [12][13][14][15]19 The present study showed no significant differences in %EWL in patients across age groups.…”
Section: Discussioncontrasting
confidence: 47%
“…Some studies have shown that older patients achieve weight loss comparable to that of younger patients. [11][12][13][14][15] Due to limited data, weight loss surgery has been underutilized among older patients due to the perceived risk of complications and poor success in postsurgical results. 16 Due to the inconsistencies in prior studies, this study evaluated presurgical comorbidities, perioperative and postoperative complications, and postsurgical outcomes (defined as percentage excess weight loss [%EWL]) of minimally invasive bariatric surgery in patients aged 55 years and older to determine if age should be used as a selection criteria for bariatric surgery.…”
mentioning
confidence: 99%
“…One patient had an elevated blood pressure postoperatively during their hospital stay, and the other reported nausea and vomiting within the first 6 weeks postoperatively. We had no reports of mortality in the Medicare age group associated with SG which is concurrent with other studies examining the same population [2][3][4]. The younger age group (n0751) had 15 major complications, but none were reported in the Medicare age group.…”
supporting
confidence: 82%
“…Some patients were able to discontinue their medications for cholesterol (60 %), diabetes (56 %), and hypertension (31 %) postoperatively, and many others were able to do dose reductions. Similarly, a study examining patients over 59 years found that 83 and 58 % of patients resolved their T2D and HTN, respectively [2], and another retrospective review found that elderly patients (>70 years) were able to reduce their medications by at least 50 % postoperatively [3].…”
mentioning
confidence: 96%
“…The short-term mortality rate was 0%. In a prospective analysis of 55 patients undergoing SG (43 were aged o58 years and 12 were aged 459 years), Leivonen et al [31] showed that older patients had a shorter operating time and a longer hospital stay (P 4 .05). Major, early-onset complications were more frequent in the older age group (42%, versus 9% in the younger group; P ¼ .02) but late complications were less common (17%, versus 44% in the younger group; P 4 .05).…”
Section: Discussionmentioning
confidence: 99%